Kinetic Study and Characterization of Nannochloropsis sp. Methyl Ester Produced Using 5Bi2O3/ZrO2 Heterogeneous Catalyst - Abd Rahman, N.J. (Nova Science Publishers, Inc., 2021)
The third-generation biodiesel from microalgae has been found to simplify the shortcomings experienced by its predecessors. In this study, biodiesel was synthesized from Nannochloropsis sp. lipid using a 5Bi2O3/ZrO2 heterogeneous catalyst. The catalyst was prepared by the incipient wetness impregnation method. The kinetic study was investigated at the various reaction temperatures to find the rate of reaction and activation energy required. It confirms that this reaction obeyed a pseudofirst order kinetics model with a calculated rate constant of 9.2 x 10-3 and activation energy of 90.71 kJ/mol. Several properties of the synthesized biodiesel were found to meet the ASTM D6751 and EN 14214 standards including cetane number, iodine value and total glycerol content. Â© 2021 by Nova Science Publishers, Inc.